Impact of the increasing use of immunosuppressants in Crohn's disease on the need for intestinal surgery. (11th January 2005) - Cosnes, J; Nion-Larmurier, I; Beaugerie, L; Afchain, P; Tiret, E; Gendre, J-P
Abstract : Background/Aim: Immunosuppressants are now used much earlier in the course of Crohn's disease; however their effect on the natural history of the disease, especially on the need for surgery, is not known. The aim of this study was to assess the evolution of the need for surgery in Crohn's disease during the last 25 years. Patients and Methods: The medical charts of 2573 patients were reviewed retrospectively. The use of immunosuppressants (azathioprine or methotrexate), the need for intestinal resection, and the occurrence of intestinal complications were assessed using Kaplan-Meier analysis in five consecutive cohorts of patients defined by the date of diagnosis of Crohn's disease (1978–82; 1983–87; 1988–92; 1993–97; 1998–2002). Results: In 565 patients seen in the authors' unit within the first three months after diagnosis, characteristics of Crohn's disease at diagnosis did not differ from one cohort to another. The five year cumulative probability to receive immunosuppressants increased from 0 in the 1978–82 cohort to 0.13, 0.25, 0.25, and 0.56 in the 1983–87, 1988–92, 1993–97, and 1998–2002 cohorts, respectively (p<0.001). Concomitantly, the cumulative risk of intestinal resection remained unchanged (from 0.35 to 0.34 at five years; p = 0.81). The cumulative risk of developing a stricturing or a penetrating intestinal complication remained also unchanged. Similar results were obtained in the 2008 patients seen during the same period who were referred to us more than three months after diagnosis. Conclusion: Although immunosuppressants have been used more frequently over the last 25 years, there was no significant decrease of the need for surgery, or of intestinal complications of Crohn's disease.